Certain Indicators of Diclofenac Sodium Pharmacokinetics in Patients with Rheumatoid Arthritis Considering Comorbide States - Nigora Tukhtaeva1, Marif Karimov2, Marina Sibirkina3, Mavluda Azimova4, Layli Khudoyberganova5, Bekh (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Much attention is paid to pharmacokinetic (FK) researches for studying the processes ofsupply, distribution, biotransformation and excretion of medications at the present time, as well as identifyinglinks between medical substances concentration and (or) its metabolites in biological fluids and tissues, andits pharmacological effect. In the treatment of rheumatoid arthritis (RA), non-steroidal anti-inflammatorydrugs (NSAID) are widely used for a symptom therapy, where Diclofenac Sodium (DS) is most commonlyprescribed. Duration of anti-inflammatory effect, effectiveness of NSAID in whole are directly dependent onthe level of effective concentration of medications and circulation duration in blood in free form.The Aim of the present research work is to study in a comparative aspect certain indicators of DiclofenacSodium pharmacokinetics in patients with rheumatoid arthritis with gastric microbiocenosis disorders(gastric dysbiosis) and without disorders (without dysbiosis).Materials and Method: 38 patients at the age from 18 to 60 years were examined, with I-II-III degree ofdisease activity. In addition to the general clinical examination, an immune-enzyme method and urease testwere carried out to determine Helicobacter Pylori and highly effective liquid chromatography to determineDiclofenac pharmacokinetics.Results: Conducted researches and analysis of their results indicate that in conditions of rheumatoid arthritis,particularly, in the presence of comorbid states, there is a decrease in the metabolism rate and an extension ofNSAID half-excretion period, which increases the risk of side effects, especially to the gastrointestinal tract,and significantly affects the disease course and the results of the treatment.Conclusion: In conditions of rheumatoid arthritis with comorbid states, there is more frequent occurrenceof the NSAID side effects. Research conducted and analysis of their results indicate that in conditionsof rheumatoid arthritis, particularly at comorbid states, there are reasonable changes in the NSAIDpharmacokinetics. The decreasing of metabolic rate and the extension of the NSAID half-excretion increasesthe risk of side effects, especially on the side of the GIT, which significantly affects the disease course andresults of the treatment. This circumstance dictates the need to take these results into account in the treatmentof the studied pathology and in the development of a personalized approach to the treatment of rheumatoidarthritis